Science and Technology from Global and Historical Perspectives - Karagözoğlu, Bahattin (Springer, 2017)
Scholarly Science (al-ilm) is a term that is used to define all of the enlightening, guiding, and refreshing knowledge. It has two main branches as the definitive (explicit) sciences and probabilistic (implicit) sciences. The probabilistic sciences alone are frequently termed as positivistic sciences and the definitive (absolute) sciences are partly covered in theology. As such, science often means information obtained and tested with the scientific methods or general truths or applications of laws. In this context, science covers all the intellectual and practical work that deal with methods (experiments, observations, and thoughts) for understanding the structure and movement of the universe including a systematic examination of the physical and natural environments. Scientific attitude is to base the behavior of a person on scientific facts with all the assessments obtained through academic studies and methods. Technology can be defined as tangible and intangible assets produced by applying mental and physical efforts to obtain a value or to improve our abilities to change the world. Developments in science trigger technological advancements and progresses in technology also provide the infrastructure necessary for the development of science.